2003
DOI: 10.2105/ajph.93.11.1858
|View full text |Cite
|
Sign up to set email alerts
|

Do Risk Factors for Childhood Infections and Malnutrition Protect Against Asthma? A Study of Brazilian Male Adolescents

Abstract: The present results are consistent with the "hygiene hypothesis," according to which early exposure to infections provides protection against asthma. The policy implications of our findings are unclear given that risk factors for asthma protect against serious childhood diseases in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
3
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 39 publications
1
29
3
1
Order By: Relevance
“…28,29 As to the occurrence of bronchiolitis in the first year of life, which was identified as risk factor for asthma in this same cohort at four years of life (12), was not associated with the outcome in the current study. Respiratory syncytial virus infection (RSV) has been strongly associated with the occurrence of wheezing and asthma in children.…”
Section: Discussionmentioning
confidence: 56%
“…28,29 As to the occurrence of bronchiolitis in the first year of life, which was identified as risk factor for asthma in this same cohort at four years of life (12), was not associated with the outcome in the current study. Respiratory syncytial virus infection (RSV) has been strongly associated with the occurrence of wheezing and asthma in children.…”
Section: Discussionmentioning
confidence: 56%
“…In contrast to our findings, a few prospective studies have reported adverse effects of breast-feeding on later wheeze or asthma risk. 7,8 In another study breast-feeding was related to increased risk of asthma in later childhood only among the subgroup of 99 children of asthmatic mothers, 6 whereas breast-feeding was not related to atopy to aeroallergens. For atopy, in unadjusted analyses we found a very slight increased risk of borderline statistical significance for 6 or more months of breast-feeding.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 However, the protective effect of breast-feeding on asthma in later childhood (age 6 years and above) is less evident, 5 and some recent studies suggest that breast-feeding actually increases the risk of asthma, wheeze, or atopy to aeroallergens at older ages. [6][7][8][9][10][11] In one study breast-feeding was associated with increased risk of asthma only in children with a family history of atopic illness. 6 Recent data suggesting that breast-feeding might enhance the risk of asthma phenotypes conflict with public health guidelines encouraging breast-feeding 1 and have raised concern among pregnant women and their physicians.…”
mentioning
confidence: 99%
“…The fact that adolescents breastfed for longer periods presented a lower prevalence of transient wheezing has preventive implications, although some authors have reported that breastfeeding is a risk factor for late-onset wheezing. (19) Another important preventive measure is smoking reduction or cessation during pregnancy. Although there was no statistical significance, the persistent and late-onset patterns were more common in children whose mothers smoked during pregnancy.…”
Section: Discussionmentioning
confidence: 99%